Evaluation of Bio-pesticides against Aphid, Hyadaphis coriandri(Das) on Coriander - Chandraker, M. K.; Prasad, Divedi; Toorray, Nitin Kumar; Ganguli, Jayalaxmi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Hyadaphis coriandri (Das) is the major species of aphid infesting coriander with a globe-wide distribution. Plant products or bio-pesticides are important alternatives to minimize the use of synthetic chemical pesticides. The present experiment was conducted during Rabi, 2023 at Pt. S.K.S. College of Agriculture and Research Station, Rajnandgaon, Chhattisgarh, in RBD design with seven treatments including six bio-pesticides and a popularly used chemical insecticide along with a control (no treatment) replicated thrice.Results revealed that in the evaluation of bio-pesticides against aphid, H. coriandri (Das) azadirachtin 0.15% (1500ppm) @ 3 ml lt-1 was found to be the second most effective bio-pesticide after the recommended chemical insecticide on coriander after both the sprays with highest yield over control (464.33 kg ha-1) and exhibited 76.89 per cent increase over control with an avoidable loss of 24.76 per cent.